Microcavity‐Stabilized Quantum Cascade Laser. Issue 1 (24th November 2015) - Siciliani de Cumis, Mario; Borri, Simone; Insero, Giacomo; Galli, Iacopo; Savchenkov, Anatoliy; Eliyahu, Danny; Ilchenko, Vladimir; Akikusa, Naota; Matsko, Andrey; Maleki, Lute; De Natale, Paolo
Abstract : Narrow linewidth lasers are key elements in optical metrology and spectroscopy. While stabilization of visible‐to‐near‐IR lasers benefits of a variety of ultrastable references, its complexity increases tremendously moving to longer wavelenghts. In this paper, mid‐IR quantum cascade laser stabilization to high‐Q crystalline microresonators is reported, a promising method for mid‐infrared metrology and on‐chip infrared spectrometers. Abstract : Narrow‐linewidth lasers are key elements in optical metrology and spectroscopy. Spectral purity of these lasers determines accuracy of the measurements and quality of collected data. Solid state and fiber lasers are stabilized to relatively large and complex external optical cavities or narrow atomic and molecular transitions to improve their spectral purity. While this stabilization technique is rather generic, its complexity increases tremendously moving to longer wavelenghts, to the infrared (IR) range. Inherent increase of losses of optical materials at longer wavelengths hinders realization of compact, room temperature, high finesse IR cavities suitable for laser stabilization. In this paper, we report on demonstration of quantum cascade lasers stabilized to high‐Q crystalline mid‐IR microcavities. The lasers operating at room temperature in the 4.3‐4.6 μm region have a linewidth approaching 10 kHz and are promising for on‐chip mid‐IR and IR spectrometers.